The effect of age, gender, income, work, and physical activity on mental health during coronavirus disease (COVID-19) lockdown in Austria - Pieh, Christoph; Budimir, Sanja; Probst, Thomas (Journal of psychosomatic research, 2020)
The impact of Coronavirus disease (COVID-19) and the governmental restrictions on mental health have been reported for different countries. This study evaluated mental health during COVID-19 lockdown in Austria and the effect of age, gender, income, work, and physical activity. An online survey was performed through Qualtrics® after four weeks of lockdown in Austria to recruit a representative sample regarding gender, age, education, and region. Indicators of mental health were quality of life (WHO-QOL BREF), well-being (WHO-5), depression (PHQ-9), anxiety (GAD-7), stress (PSS-10), and sleep quality (ISI). In total, N = 1005 individuals were included (53% women). 21% scored above the cut off ≥10 points (PHQ-9) for moderate depressive symptoms, 119% scored above the cut-off ≥10 points (GAD-7) for moderate anxiety symptoms, and 16% above the cut-off ≥15 points (ISI) for clinical insomnia. ANOVAs, Bonferroni-corrected post-hoc tests, and t-tests showed highest mental health problems in adults under 35 years, women, people with no work, and low income (all p-values <.05). Comparisons with a large Austrian sample recruited within the ATHIS 2014 study showed increases of depression and decreases of quality of life in times of COVID-19 as compared to before COVID-19. Depressive symptoms (21%) and anxiety symptoms (19%) are higher during COVID-19 compared to previous epidemiological data. 16% rated over the cut-off for moderate or severe clinical insomnia. The COVID-19 pandemic and lockdown seems particularly stressful for younger adults (<35 years), women, people without work, and low income. •Higher prevalence of mental health problems during COVID-19 in Austria.•Depressive symptoms are up to five times more prevalent compared to pre-corona times.•Anxiety symptoms are up to three times more prevalent compared to pre-corona times.•Quality of Life and well-being is lower compared to pre-corona times.